Market Orientation's Neglected Role in Marketing Exploitation and Exploration Tradeoffs - Zainul Wasik; Candraningrat; Muchammad Saifuddin (Journal of Managerial Sciences and Studies, 2023)
The goal of marketing exploitation methods, sometimes referred to as marketing exploration, can be to increase the company's knowledge and capabilities or to improve its current capabilities. According to a study on organisational strategy and learning, using both strategies can compromise each company's operational processes and harm its financial success. Market organisation, in our opinion, facilitates the flow of market information between the two strategy processes, integrates the two strategies by acting as a dynamic market, and aids businesses in integrating marketing exploitation and exploration strategies. Using complementary high-level marketing exploration and marketing exploitation strategies, companies with strong market orientation can improve the financial performance of new products, as measured at two different points in time, according to a study of the packaged food industry in Indonesia. However, as the trade-off foresees, businesses with a poor market orientation are unable to benefit from these techniques.